Kejadian Skabies di Beberapa Pondok Pesantren Kota Banjarbaru - Mifta Rahman Santoso; Noraida Noraida; Abdul Khair (Jurnal Kesehatan Indonesia, 2021)
Scabies is known in Indonesia as scurvy. Scabies is an infectious disease that can be transmitted directly or indirectly. It can be found in densely populated places. Therefore, students who live in Islamic boarding schools are important subjects in this problem. This study aimed to determine the relationship between sanitation and the incidence of scabies in several Islamic boarding schools in Banjarbaru City. This study used an analytical study design that linked sanitation with the incidence of scabies in several Islamic boarding schools in Banjarbaru city. The data was analyzed using the correlation test (Pearson Product Moment). The results showed that food and beverage management had a significant association with the incidence of scabies in several Islamic boarding schools in Banjarbaru city. Other variables had no association with the incidence of scabies. The correlation test results showed that no significant relationship between sanitation and the incidence of scabies in several Islamic boarding schools in Banjarbaru city in 2020 with a p-value of 0,073. Efforts that can be made to reduce the incidence of scabies are maintaining and paying attention to sanitation, especially in the management of food and beverages, maintenance of equipment used for cooking, and sanitation facilities.